KHAZANAH TAFSIR NUSANTARA: KAJIAN ATAS PENAFSIRAN NAWAWI BANTEN TERHADAP SURAH AL- FATIHAH DALAM MARAH LABID - Tsalis Muttaqin (MAGHZA, 2017)
Some of the well known Ulamas in the world have born in this country. They have born in the Nusantara Archipelago. They have spent their younger time to study with Ulama in their home villages. After that, they have continued to study to the Middle East Countries, especially to Mecca. In Mecca, they have also well acknowledged by the local people as influenced Ulama. Muhammad Nawawi> bin Umar al- Bantani al-JÄwÄ«, one of the Ulama from Indonesia, has well known by the Middle East people. He was born in Serangâ€™s regency, Banten. He has well known as one of the active Ulama who was very active to produce various works. There were many books written in the Arabic language by him. There were more than 80 books written by Nawawi>. One of his famous works is Qurâ€™anic interpretation entitled MarÄh LabÄ«d. The data gathered by the author showed that there were three (3) famous publishers in the Middle East that continually published this book. Some of the publishers in Indonesia also published this book. MarÄh LabÄ«d has been used by some of the Pesantren and Madrasah in Indonesia as their primer sources. Anyhow, this paper will discuss deeply on Nawawi>â€™s interpretation on al-FÄtih}ah. Beside of well known as opening surah in the Holy Qurâ€™an, al-Fatihah also relatively shorter, just seven verses. In order to be found the deeper discussion on how Nawawi> conducted interpretation on Quranic verses.